Вплив цереброкурину і тіоцетаму на ранню відповідь геному та морфофункціональний стан нейронів СА-1 зони гіпокампа щурів за умов пренатальної алкоголізації - Єгоров, Олександр Миколайович; Бєленічев, Ігор Федорович; Соколик, Олена Петрівна; Абрамов, Андрій Володимирович; Egorov, A. N.; Belenichev, I. F.; Sokolik, E. Р.; Abramov, A. V. (My University, 2012)
Проведенными экспериментальными исследованиями установлено, что пренатальная алкоголизация крыс приводила к изменению ответа генома, проявляющегося нарушением экспрессии генов раннего реагирования c-fos, уменьшением плотности и площади нейронов и глиальных клеток СА-1 зоны гиппокампа, а также уменьшением содержания в них РНК. 25-дневное курсовое введение новорожденным, которые перенесли пренатальную алкоголизацию, тиоцетама и цереброкурина оказывало равнонаправленный нейропротективный эффект, который выражался в увеличении плотности и площади нейронов в СА-1 зоне гиппокампа, а также содержания в них РНК. Введение по такой же схеме пирацетама не оказало подобного нейропротективного эффекта. There were established that prenatal alcoholization of rats caused significant changes in the response of the genome, which is manifested in the violation of the genes early response c-fos expression, decrease of density and area of neurons and glial cells from the CA-1 zone of the hippocampus and also their RNA contents. 25-days course administration of tiocetam to the newborn rats who were undergone to prenatal alcoholization caused the same neuroprotective effect (increase of the density and the square of neurons as well as RNA content) as cerebrocurin did. Introduction of piracetam according to the same scheme did not show such a reliable neuroprotective effect.
The impact of cerebrocurin and tiocetam on the early response of the genome and morphofunctional state of neurons from CA-1 zone of the hippocampus of rats under prenatal alcoholization
Keywords: пренатальна алкоголізація; тіоцетам; цереброкурин; ген раннього реагування c-fos; СА-1 зона гіпокампа; prenatal alcoholization; tiocetam; cerebrocurin; gene of early response c-fos; CA-1 zone of the hippocampus